16th AIAA Aviation Technology, Integration, and Operations Conference 2016
DOI: 10.2514/6.2016-3143
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Systems Architecting - a Functional-Logical Domain Perspective

Abstract: Presented is a novel framework for early systems architecture design. The framework defines data structures and algorithms that enable the systems architect to operate interactively and simultaneously in both the functional and logical domains. A prototype software tool, called AirCADia Architect, was implemented, which allowed the framework to be evaluated by practicing aircraft systems architects. The evaluation confirmed that, on the whole, the approach enables the architects to effectively express their cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The architects' feedback indicated that, on the whole, the approach enables the architects to effectively express their creative ideas when synthesizing architectures, and was especially acknowledged as the way forward for rationale capture 4 …”
Section: Illustrative Examplementioning
confidence: 99%
See 1 more Smart Citation
“…The architects' feedback indicated that, on the whole, the approach enables the architects to effectively express their creative ideas when synthesizing architectures, and was especially acknowledged as the way forward for rationale capture 4 …”
Section: Illustrative Examplementioning
confidence: 99%
“…In this paper, we shall distinguish between logical and physical domains, where the former is assumed to be concerned mainly with the interconnectivity between components and subsystems, while the latter with spatial layout and geometry. In a recent publication, 4 we presented data structures underpinning basic operations that take place in the F‐L domains. Here, we extend that work to include requirements and the notion of a computational (behavioral) domain.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 4, the sets of parameters for the input and output ports are represented by and , respectively, as shown in Eq. 1and (2). A component has its own parameters, referred to as component-parameters, represented by the set, as shown in Eq.…”
Section: Proposed Approachmentioning
confidence: 99%
“…It is assumed that the architecting takes place in four domains: Requirement, Functional, Logical and Physical (RFLP) 1 . In a recent work, Guenov et al 2 specified the interface between the functional and logical views. Their approach is extended here to include sizing and is restricted to the systems requirements and logical representations as the input to the systems sizing process.…”
Section: Introductionmentioning
confidence: 99%
“…Their FD is problem-specific, as is the analysis method, and therefore not easily generalized. The same holds for AirCADia [8], which breaks down the system description into a functional and logical domain and proceeds by mapping functions to means to arrive at a system synthesis. Where others start off with a FD, Yuan et al [9] developed a method to automate the FD process itself, which may be useful for end-users to specify their intentions when modeling a system.…”
Section: Introductionmentioning
confidence: 99%